Implementation of a Standardized Protocol for Hospitalized Patients Who Inject Drugs and Require Long-Term Antibiotics Reduces Length of Stay Without Increasing 30-Day Readmissions. (4th October 2017) - Rolfe, Robert J; Mathews, Ronnie E; Rodriguez, J Martin; Paddock, Cayce S; Lane, Peter S; Taylor, Benjamin B; Lee, Rachael A
Abstract: Background: Injection drug use (IDU) is a growing epidemic, and persons who inject drugs (PWID) are at high risk for infection. IDU is a barrier to outpatient parenteral antimicrobial therapy (OPAT) and provider experience and knowledge may lead to variation in patient care. Recognizing this problem, a multi-disciplinary team implemented a protocol for management of PWID requiring IV antibiotics. The main goals were to standardize the evaluation and risk assessment of PWID with infections and to provide substance abuse counseling and treatment in order to decrease length of stay (LOS). Methods: A protocol was developed outlining the evaluation, diagnosis, risk-assessment, treatment, maintenance, and follow up of PWID requiring prolonged IV antibiotics (Figure 1). Patients meeting inclusion criteria were identified and the multidisciplinary team assessed the patient. ID confirmed the diagnosis and outlined the treatment plan, and addiction medicine performed a 9-point risk assessment. Low-risk patients were discharged to complete OPAT. Medium risk and high-risk patients remained hospitalized and were offered group therapy, opioid replacement therapy if applicable, and were reassessed weekly for discharge. These patients were compared with previously identified PWID requiring antibiotics prior to the protocol implementation. Results: 37 patients pre-protocol were compared with 34 patients following implementation. Demographics were similar except 56% of the post-implementation group were diagnosed with a concomitant psychiatric disorder vs. 27% in the pre-implementation group (P = 0.01). There was no statistical difference between the number of patients who left AMA in either group (13.5 % pre; 23.5% post; p 0.28) or the number of readmissions (51.4% pre; 32.4% post; P = 0.10). However, the median LOS was significantly reduced in the post implementation group (18. days vs. 42 days; P <0.001). There have been 418 hospital days saved post implementation. Conclusion: Implementation of a standardized protocol with a multidisciplinary team and risk stratification to determine appropriate patients for discharge has led to improvement in LOS as well as improved addiction care for hospitalized PWID requiring long-term antibiotics. Disclosures: All authors: No reported disclosures.